2023
DOI: 10.32938/jpm.v4i2.3573
|View full text |Cite
|
Sign up to set email alerts
|

Profil Metakognisi Siswa SMP Dalam Menyelesaikan Soal Matematika Tipe High Order Thinking Skills Ditinjau Dari Adversity Quotient

Abstract: Tujuan penelitian ini adalah mendeskripsikan bagaimana profil metakognisi siswa dalam menyelesaikan masalah matematika tipe HOTS ditinjau dari Adversity Quotient (AQ). AQ adalah tingkat kecerdasan seseorang dalam menghadapi masalah. Adapun subjek dalam penelitian ini adalah siswa kelas 8 SMP yang dipilih melalui teknik purposing sample berdasarkan hasil tes ARP (Adversity Respons Profile) di level AQ sedang (camper) dan level AQ tinggi (climber). Objek dalam penelitian ini adalah kemampuan metakognisi siswa da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Next, research the metacognitive profile of high school students in class XI science in solving mathematical problems about probability (Lestari, 2017). Researchers have also conducted several similar studies, namely about students' metacognitive activities in solving linear programming problems in terms of gender differences (Kartika, 2020) and the metacognitive profile of junior high school students in solving HOTS-type mathematics problems in terms of adversity quotient (Kartika et al, 2023). From the explanation above, research with student subjects is still rarely found, so the researcher intends to combine several previous studies with different research subjects, namely student subjects, in solving problems related to ELA in terms of one type of cognitive style, namely tempo conceptual cognitive style.…”
Section: Introductionmentioning
confidence: 99%
“…Next, research the metacognitive profile of high school students in class XI science in solving mathematical problems about probability (Lestari, 2017). Researchers have also conducted several similar studies, namely about students' metacognitive activities in solving linear programming problems in terms of gender differences (Kartika, 2020) and the metacognitive profile of junior high school students in solving HOTS-type mathematics problems in terms of adversity quotient (Kartika et al, 2023). From the explanation above, research with student subjects is still rarely found, so the researcher intends to combine several previous studies with different research subjects, namely student subjects, in solving problems related to ELA in terms of one type of cognitive style, namely tempo conceptual cognitive style.…”
Section: Introductionmentioning
confidence: 99%